Constraints in Utilizing Local Legend in Strengthening Literature Movement of Elementry School Students in Aceh Besar - Asriani Asriani; Cut Fauziah; Rini Nurul Amla; Nurul Azmi; Junaidi Junaidi (Universitas Serambi Mekkah, 2022)
The use of local legends is very good in strengthening the student literacy movement. This study aims to describe the obstacles in the use of local legends in strengthening the literary literacy movement of elementary school students in Aceh Besar District. This type of research includes a qualitative description. The data was obtained through direct observation of the availability of information about local legends in Aceh Besar District, such as Batu Bertutup, Eumpee Buno, Mon Twi Patong, Amat Rhang Manyang and Asal-Usul Gunung Tiga. Based on the results of the study, several obstacles were found in the use of local legends, namely (1) loose customary ties in society and the indifference of the younger generation to folk legends; (2) local legend books have not been recorded yet; (3) lack of concern for and pride in local legends; (4) generally storytellers are old and have died. Keywords: Constraints, Utilization, Local Legends, Literary Literacy Movement